Economic evaluation of second measles containing vaccine (MCV) dose: a systematic review of available evidence - Samuel Bawa; Abrham Wondimu; Maarten J. Postma; Raymond Hutubessy; Marinus van Hulst (Taylor & Francis Group, 2024)
Introduction The global measles incidence has decreased from 145 to 49 cases per 1 million population from 2000 to 2018, but evaluating the economic benefits of a second measles-containing vaccine (MCV2) is crucial. This study reviewed the evidence and quality of economic evaluation studies to guide MCV2 introduction.Methods The systematic review of model-based economic evaluation studies was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The search yielded 2231 articles, with 876 duplicates removed and 1355 articles screened, with nine studies included for final analysis.Results Six studies reported a positive benefit-cost ratio with one resulting in net savings of $11.6 billion, and two studies estimated a 2-dose MMR vaccination program would save $119.24 to prevent one measles case, and a second dose could prevent 9,200 cases at 18 months, saving $548.19 per case. The most sensitive variables were the discount rate and vaccination administration cost.Conclusions Two MCV doses or a second opportunity with an additional dose of MCV were highly cost-beneficial and resulted in substantial cost savings compared to a single routine vaccine. But further research using high-quality model-based health economic evaluation studies of MCV2 should be made available to decision-makers.PROSPERO Registration CRD42020200669